Dari Ritual Menuju Perubahan Sosial: Kritik Hassan Hanafi Terhadap Formalisme Agama Di Indonesia - Titiya Utami (4, 2025)
This study analyzes Hassan Hanafi's critique of religious formalism and its relevance to the religious practices of Indonesian Muslim society. The significant proliferation of religious formalism indicates a reduction of religious understanding to ritualistic-symbolic aspects while neglecting ethical-transformative dimensions. Through a qualitative library research approach with content analysis, this study explores Hanafi's construction of liberation hermeneutics, sacred-profane dialectics, and anthropocentric tawhid as the basis for critiquing religious ritualization. Findings reveal that manifestations of religious formalism in Indonesia are embodied in the paradox between individual piety and social piety, reinforced by structural factors such as ritualistic education systems and the instrumentalization of religion in identity politics. Hanafi's thought offers a theoretical framework for transforming the religious paradigm toward substantive and emancipatory approaches, yet faces complex epistemological, sociological, and cultural obstacles. This research contributes to the development of progressive Islamic discourse in Indonesia by emphasizing the urgency of integrating spirituality with transformative action for social justice. Abstrak Penelitian ini menganalisis kritik Hassan Hanafi terhadap formalisme agama dan relevansinya dalam konteks praktik keberagamaan masyarakat Muslim Indonesia. Formalisme agama yang mengalami proliferasi signifikan mengindikasikan reduksi pemahaman keagamaan pada aspek ritualistik-simbolik dengan mengabaikan dimensi etis-transformatif. Melalui pendekatan kualitatif library research dengan analisis konten, penelitian ini mengeksplorasi konstruksi pemikiran Hanafi tentang hermeneutika pembebasan, dialektika sakral-profan, dan tauhid antroposentris sebagai basis kritik terhadap ritualisasi agama. Temuan menunjukkan bahwa manifestasi formalisme agama di Indonesia terwujud dalam paradoks antara kesalehan individual dan kesalehan sosial, diperkuat oleh faktor struktural seperti sistem pendidikan yang ritualistik dan instrumentalisasi agama dalam politik identitas. Pemikiran Hanafi menawarkan kerangka teoretis untuk transformasi paradigma keberagamaan menuju yang substantif dan emansipatoris, namun menghadapi hambatan epistemologis, sosiologis, dan kultural yang kompleks. Penelitian ini berkontribusi pada pengembangan wacana Islam progresif di Indonesia dengan menekankan urgensi mengintegrasikan spiritualitas dengan aksi transformatif untuk keadilan sosial